Population‐relevant endpoints in the evaluation of endocrine‐active substances (EAS) for ecotoxicological hazard and risk assessment. (27th February 2017) - Marty, Mary S; Blankinship, Amy; Chambers, Janice; Constantine, Lisa; Kloas, Werner; Kumar, Anupama; Lagadic, Laurent; Meador, James; Pickford, Daniel; Schwarz, Tamar; Verslycke, Tim
ABSTRACT: For ecotoxicological risk assessment, endocrine disruptors require the establishment of an endocrine mode of action (MoA) with a plausible link to a population‐relevant adverse effect. Current ecotoxicity test methods incorporate mostly apical endpoints although some also include mechanistic endpoints, subcellular‐through‐organ level, which can help establish an endocrine MoA. However, the link between these endpoints and adverse population‐level effects is often unclear. The case studies of endocrine‐active substances (EAS) (tributyltin, ethinylestradiol, perchlorate, trenbolone, propiconazole, and vinclozolin) evaluated from the Society of Environmental Toxicology and Chemistry (SETAC) Pellston Workshop ® "Ecotoxicological Hazard and Risk Assessment Approaches for Endocrine‐Active Substances (EHRA)" were used to evaluate the population relevance of toxicity endpoints in various taxa according to regulatory endocrine‐disruptor frameworks such as the Organisation for Economic Co‐operation and Development (OECD) Conceptual Framework for Testing and Assessment of Endocrine Disruptors. A wide variety of potentially endocrine‐relevant endpoints were identified for mollusks, fish, amphibians, birds, and mammals, although the strength of the relationship between test endpoints and population‐level effects was often uncertain. Furthermore, testing alone is insufficient for assessing potential adaptation and recovery processes in exposed populations. For this purpose, models that link effects observed in laboratory tests to the dynamics of wildlife populations appear to be necessary, and their development requires reliable and robust data. As our understanding of endocrine perturbations and key event relationships improves, adverse population‐level effects will be more easily and accurately predicted. Integr Environ Assess Manag 2017;13:317–330. © 2017 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: For ecotoxicological risk assessment, endocrine disrupters require the establishment of an endocrine mode of action (i.e., mechanistic endpoints) with a plausible linkage to a population‐relevant adverse effect. Case study chemicals were used to evaluate the population relevance of toxicity endpoints in various taxa according to regulatory endocrine disruptor frameworks. Potential endocrine‐relevant endpoints were identified for mollusks, fish, amphibians, birds and mammals, although the strength of the relationship between test endpoints and population‐level effects was often uncertain. Models that link effects observed in laboratory tests to the dynamics of wildlife populations appear to be necessary to clarify the relationship between some altered endpoints and population‐level effects.